A Study on the Work Related Stress for HR Manager: Understanding and Managing Work Related Stress in HR Management (Journal of Advances and Scholarly Researches in Allied Education, 2019)
To define the term, stress in an employee arises from the situation where work demands, exceeds the capability and capacity of the individual. In a scenario, where the company is expecting ‘too much’ from the employee, irrespective of their capability and efficiency, it leads to work related stress. Often, unclear goals and duties, and bullying or harassment are related to the causes of work related stress in employees. This is a significant reason behind diseases and illness in employees, and is often correlated with the staff turnover, higher rates of employee absenteeism, and other key indicators of underperformance.To cope up with stress in employees, it is important to take effective actions.